Thermal feature-size enhancement in multiphoton photoresists - Liaros, Nikolaos; Tomova, Zuleykhan; Gutierrez Razo, Sandra A.; Bender, John S.; Souna, Amanda J.; Devoe, Robert J.; Ender, David A.; Gates, Brian J.; Fourkas, John T. (Frontiers in Nanotechnology, 2022)
We demonstrate a new approach for decreasing the feature size in multiphoton absorption polymerization (MAP). Acrylic photoresists containing the photoinitiator KL68 (bis-[4-(diphenylamino) stryl]-1-(2-ethylhexyloxy), 4-(methoxy)benzene) exhibit a proportional velocity (PROVE) dependence, yielding smaller feature sizes at lower fabrication speeds. The feature size in this photoresist decreases substantially with a temperature increase of less than 10°C when all other fabrication parameters are kept constant, suggesting that the PROVE behavior results from local heating. Although higher temperatures have previously been associated with decreased feature sizes in MAP, the effect observed here is considerably stronger than in previous work, and is shown to be a property of the photoinitiator. This discovery opens the door to exploiting thermal gradients to improve resolution in MAP lithography.